Implementation of A Deep Learning Approach to Improve the Learning Outcomes of Students in the Building Design, Modeling and Information Department at State Vocational High School 1 Kaidipang - Sri Astuti Binol; Hiskia Kamang Manggopa; Harrychoon Angmalisang; Parabelem Tinno Dolf Rompas (JR Education, 2025)
The low level of Higher Order Thinking Skills (HOTS) and student learning outcomes in vocational subjects remains a major challenge in vocational education in Indonesia. Students generally operate at the level of Lower Order Thinking Skills (LOTS) and have difficulty connecting vocational concepts with their application in real-world contexts. This study aims to improve student learning outcomes through the implementation of a Deep Learning approach in vocational instruction at the Building Modeling and Information Design (DPIB) Department of SMK Negeri 1 Kaidipang. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles comprising planning, action, observation, and reflection stages. The research participants consisted of 10 Grade X DPIB students. The Deep Learning approach was implemented through inquiry learning and project-based learning methods. The results demonstrate a significant improvement in learning outcomes, with average scores increasing from 42% in the pre-cycle to 66% in Cycle I and 86% in Cycle II. Improvements were also observed in collaboration, conceptual understanding, critical analysis skills, and student engagement.